Uterine Rupture due to Gestational Trophoblastic Neoplasia on Nulliparous Woman : A Case Report - Milano, Deo Cerlova; Muhammad, SpOG(K)-Onkogin, Dr. dr. Syamel (Andalas Obstetrics And Gynecology Journal, 2022)
Background : Invasive mole (IM) is a frequent complication of gestational tropoblastic neoplasia (GTN). These tissues invade the myometrium deeply, occasionally affecting the peritoneum or vaginal vault. The prevalence of an invasive mole causing uterine rupture is uncommon.  Case Report : We discuss the case of a 46-year-old nulliparous woman who presented to the emergency room complained severe abdominal pain that had been present for 4 hours. Patient had a history of complete mole evacuation 2 months ago with persistently elevated beta-human chorionic gonadotropin (B-HCG). .  The patient was diagnosed with suspected uterine rupture due to an invasive mole   and advised to undergo hysterectomy. Total abdominal hysterectomy was performed with the preservation of both ovaries. Choriocarcinoma was diagnosed histopathologically, and the patient was prepared for chemotherapy using EMA-CO protocols. Conclusion :  Perforation of the uterus by an invasive mole is a rare but lethal complication. Although hysterectomy followed by chemotherapy is the standard treatment for this condition, several studies demonstrate the benefit of conservative management in terms of fertility preservation in reproductive-aged women.